Concordance of Fathers and Mothers in the Assessment of Their 5-Year-Old Child's Dental Fear - Sanna Seppänen; Kukka Vuorenmaa; Auli Suominen; Mika Ogawa; Vesa Pohjola; Kari Rantavuori; Hasse Karlsson; Linnea Karlsson; Satu Lahti (MDPI AG, 2024)
The aim of this study was to evaluate the concordance of parents' assessments of their child's dental fear. Cross-sectional secondary analysis used data from the multidisciplinary FinnBrain Birth Cohort Study. Child dental fear was assessed at age 5 with the Finnish translation of the modified Children's Fear Survey Schedule Dental Subscale (CFSS-M) by both fathers (n = 588) and mothers (n = 1100). Reply alternatives were from 1 = not afraid to 5 = very afraid and 6 = no experience coded as missing and 1. In total, 514 mother-father pairs were eligible for the analyses. Descriptive statistics, percentage agreement and Cohen's Kappa coefficients were used in the analyses. The concordance of parents' assessments was poor (Kappa range 0.072-0.258). The majority of parents replied "No Experience" to items related to invasive treatment or being unable to breathe. Thus, coding of this reply alternative had a significant impact on the mean values of the child's fear. When assessing the fear of a five-year-old child, it might not be safe to rely only on one parent's assessment, and whether or not the child has experience with the question asked should also be considered.